2022
DOI: 10.17509/ijal.v12i1.46896
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Madurese dialect toward students’ English word stress production

Abstract: Communication using English in Indonesia is challenging, especially when English is not used frequently. It’s happen to some area where English is only taught as mandatory subject in high schools. Madura is one of island in East Java that has unique characteristic, especially in the native language. This study aimed to analyze the misplaced of English word stress done by Madurese students and to find out the reason why they frequently misplace the word stress. A questionnaire and recording were used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is also necessary for the instructor. Teachers with empathy are more effective with all of their students in sharing the ideas (Puspandari & Basthomi, 2022). It helps to create a positive learning atmosphere in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…It is also necessary for the instructor. Teachers with empathy are more effective with all of their students in sharing the ideas (Puspandari & Basthomi, 2022). It helps to create a positive learning atmosphere in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…It is because the EFL learners' first language is different from English in term of pronunciation. Puspandari & Basthomi (2022) investigated the incorrect production of English word stress by the Madurese high school students. Widagsa et al (2019) concluded that the learners could not consider the importance of stress words while speaking English.…”
Section: Introductionmentioning
confidence: 99%